2021
DOI: 10.1016/j.jocn.2021.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgeons’ opinions on discussing sexual health among brain tumor patients: Room for improvement?

Abstract: Background: As sexual health is an important aspect of general quality of life, discussing and treating sexual health issues should also be part of the oncological care given to patients. It is unknown to what extent neurosurgeons discuss sexual health issues with patients suffering from brain tumors. Methods: A 25-question survey was sent to members of the Congress of Neurological Surgeons by email.Results: Of all neurosurgeons who replied, 59.1% never discussed sexual health with patients suffering from brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We identified a total of three [ 10 , 24 , 25 ] studies, which address SD incidence and/or associations between SD and QoL ( Figure 1 ). Handsearching of articles revealed 60 additional articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified a total of three [ 10 , 24 , 25 ] studies, which address SD incidence and/or associations between SD and QoL ( Figure 1 ). Handsearching of articles revealed 60 additional articles [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ...…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, as LGG patients are of childbearing age, the desire for pregnancy and hence fertility preservation (FP) should also be discussed during this interview [ 13 ]. Given the difficulties in carrying out those interviews, it is not surprising that Laldjising et al [ 26 ] reported that nearly 60% of interrogated neurosurgeons treating brain tumor patients never discussed sexual health with them, claiming that lack of knowledge and insufficient time were the main reasons. Discussing sexual health with tumor patients appears to also be challenging in clinical routine for oncologists and radiotherapists [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient time during visits (46.6%), followed by patients' embarrassment (44.8%), and lack of training, are the most important reasons that contributed to not assess SD in the daily practice. On the contrary other healthcare professionals as well as gastroenterologists, car-diologists, nephrologists, neurologists, and neurosurgeons reported that the most important reasons are lack of knowledge and training, insufficient time during the visits and embarrassment (19). Despite these, 34.4% of rheumatologists are conscious that a specific training in sexual medicine could be useful in SD treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the evidence shows that it is also a neglected problem in other specialist fields such as cardiology, neurology and gastroenterology. Several reasons such as lack of knowledge/training, lack of time during visits, and embarrassment have been reported (16)(17)(18)(19)(20). To the best of our knowledge, there are no study evaluating how the rheumatologists discuss and manage their patients' sexual problems.…”
Section: Introductionmentioning
confidence: 99%
“…Unfamiliarity with the concept of "moral distress" may have reduced responses, but our response rate (5.8%) aligns with that of recent Congress of Neurological Surgeons member surveys (2.2%-8.0%). 42,43 Second, we defined "morally injured" neurosurgeons as those contemplating leaving a position because of moral distress. This definition may be too narrow and underestimate moral injury.…”
Section: Limitationsmentioning
confidence: 99%